2013
DOI: 10.1021/ie301234b
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Effects on the Kinetics of Enzymatic Hydrolysis of Avicel for Batch Production of Cellulosic Ethanol

Abstract: This article presents a tightly coupled experimental and theoretical study to explore the effects of mixing and mass transfer on the kinetics and dynamics of cellulase-mediated cellulose (Avicel) hydrolysis for bioethanol production in batch reactors. The kinetic parameters (K M and V Max) for the three enzymes (endoglucanase, exoglucanase, β-glucosidase) that constitute cellulase are determined at various mixing speeds: 0 (no mixing), 40, 80, and 150 rpm (high mixing). The experimental values of K M and V Max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Further studies would be necessary to give a sound explanation of the kinetic reaction behavior in the OFB. It has previously been suggested in that lower mixing speed leads to higher glucose yield, although the authors just worked in the range of 0 to 160 rpm. Interestingly, the lowest mixing showed fastest glucose production in the first hours, but almost no further conversion after 1000 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies would be necessary to give a sound explanation of the kinetic reaction behavior in the OFB. It has previously been suggested in that lower mixing speed leads to higher glucose yield, although the authors just worked in the range of 0 to 160 rpm. Interestingly, the lowest mixing showed fastest glucose production in the first hours, but almost no further conversion after 1000 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The improvements of initial good mixing become obvious only in the later course of the hydrolysis. The published modeled kinetic factors suggest a strong decay of rate constants for endo‐ and exoglucanase up to 100 rpm, and subsequent increase with highest rate constant >700 rpm. Earlier studies have suggested that initial mixing is crucial for hydrolysis performance to efficiently distribute the enzymes, while others highlighted that periods of vigorous mixing are sufficient .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using equations (2) to (8), mass transfer coefficient (k C ) values were estimated for runs 1 to 9 at different times. Results of these calculations are shown in Figure 3.…”
Section: Mass Transfer Rate Evaluationmentioning
confidence: 99%
“…(Gaikwad and Chakraborty, 2013); what is the optimally mixed reactor configuration for enzymatic hydrolysis in continuous systems? (Chakraborty et al, 2010);(c) what is the optimal reactor mixing strategy for batch hydrolysis of cellulose?…”
Section: Introductionmentioning
confidence: 99%